2020
DOI: 10.1007/s42729-020-00274-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Application of Chemical and Organic Fertilizers on Bacterial Diversity of Cornfield Soil in a Karst Area

Abstract: Among karst mountain agricultural fertilization measures, the partial replacement of chemical fertilizers with organic fertilizers is important for protecting its vulnerable mountain environment and developing ecologically-friendly agriculture. In this study, we investigated the effects of short-term organic fertilizer application on the bacterial diversity of maize soil in karst areas and the potential of using organic fertilizer as a partial substitute for chemical fertilizers. Two maize fields with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
0
19
1
Order By: Relevance
“…Modern agricultural systems rely heavily on synthetic fertilizers and agrochemicals [ 8 ]. Fertilizer is one of the most important inputs, accounting for approximately a third of the total cost of cultivation [ 9 ]. The fast depletion of nitrogenous, phosphatic, and potassic reserves because of extreme usage is a cause of grave concern for countries that are yet to achieve food security [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern agricultural systems rely heavily on synthetic fertilizers and agrochemicals [ 8 ]. Fertilizer is one of the most important inputs, accounting for approximately a third of the total cost of cultivation [ 9 ]. The fast depletion of nitrogenous, phosphatic, and potassic reserves because of extreme usage is a cause of grave concern for countries that are yet to achieve food security [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of fertilizer treatments on microbial diversity have been well studied ( 21 , 22 ). Short-term organic fertilizer treatment increased the bacterial richness significantly, especially for some functional bacteria in Karst areas, such as Nitrospira and Gemmatimonas ( 23 ). Large amounts of chemical fertilizers have been applied to arable fields over the past few decades to prevent food shortages worldwide and maximize crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…Increased OFs application can increase soil carbon storage and plant nutrients, and improve soil biological activity, which are of great significance for mitigating climate warming and developing sustainable agricultural production ( Gattinger et al, 2012 ; Seufert et al, 2012 ). Many studies have shown that OFs application is an effective way to improve crop yield and quality ( Liu et al, 2020 , 2021 ; Du et al, 2022 ), and increase soil microbial richness and diversity ( Zhou et al, 2015 ; Cui et al, 2018 ; Li et al, 2020 ). However, the contents of mineral nutrients such as nitrogen, phosphorus, and potassium in OFs are low, and the increased amount of fertilizer needed increases the cost and application difficulty.…”
Section: Introductionmentioning
confidence: 99%